(untitled) (E Conference Zone, 2022)
This scientific article provides an analysis of the principles of organization and functioning of a joint stock company in Republic of Uzbekistan. The article was substantiated features of the activities of joint stock companies (JSCs), also developed scientific and practical conclusions.